2008
DOI: 10.1159/000129671
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal Description of the Maternal Surface of the Placenta

Abstract: Background: Recently, multifractal analysis based on generalized concepts of fractals has been applied to biological tissues composed of complex structures. Methods: Using digitized images of the maternal surface of 278 placentas, multifractal parameters were measured with a fractal analysis software. Results: The values of αmin, α(0), αmax and the degree of multifractality given by the αmax – αmin difference calculated from 278 placentas were 1.840 ± 0.068, 2.089 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…also affect placental and fetal growth. A recent report using a new mathematical method of multifractal analysis has shown that placentas with PIH or FGR possess different structural patterns 13 . Therefore, there may be some differences in placental growth patterns throughout gestation among these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…also affect placental and fetal growth. A recent report using a new mathematical method of multifractal analysis has shown that placentas with PIH or FGR possess different structural patterns 13 . Therefore, there may be some differences in placental growth patterns throughout gestation among these conditions.…”
Section: Discussionmentioning
confidence: 99%